Manifestos do coração: significados da cirurgia cardíaca para pacientes pré e pós-cirúrgicos - Wottrich, Shana Hastenpflug (2011)
Cardiac surgery is an event of important consequences as concerns the lives of people who go through it, both in the physiological and psychological aspects. Thus, the research from which the present master‟s thesis was originated had as its aim to understand the meanings that pre and post surgical patients attribute to their experiences. It is a clinical qualitative research, of exploratory and descriptive character, with 28 patients (14 presurgical and 13 postsurgical), who were users of a cardiology outpatient clinic of a university hospital in the interior of Rio Grande do Sul. The number of participants was reached through saturation criterion. Semi-structured interviews and autophotography were used for data collection. Analysis was carried out through content analysis and using an itinerary as regards the content analysis of the images. Categories that were originated from data analysis are described and discussed in four articles, that compose the main component of this thesis. Results point out that surgery does not only mobilize the physical body, but regards implications in the lives of such patients, concerning their meanings about themselves and the others. Acceptance of the cardiac disease was identified as a complex process, that involves a commitment among different symbolic universes and implies, for the patient, the impossibility of carrying out one‟s routine. The symptoms of the disease are most of the times not perceivable by the patient. He has to accept that other person identifies his condition through exams and medical procedures. Besides, accepting the disease means to accept finitude of life and of the potentiality of the body. Such situation seems to happen in an ambivalent way, and the confrontation with reality is intensified when there is an indication for the surgical procedure. Surgery gives rise to fantasies and fears that permeate plans and routine, imposing a situation where life and death are at stake. After the procedure, recognition of the self and of the limits of the body seems to happen. It is an experience of adequating the expectancies prior to surgery, that seems to depend on the references of each person about the process. Therefore, there are important movements of reflection, in which the subjects evaluate their lives and their implications as protagonists of them. Religiosity seems to underlie many of the reported experiences, since patients use their beliefs to search for a meaning concerning their experiences. Results point out that the surgical procedure is an experience underlied by intense feelings of helplessness and suffering. Thus, the meanings given to such reality by the patients should be more broadly understood by the health team that cares for them. Thus, it would be possible to build knowledge that may flow in the interface of the medical and layman universes, creating a commitment between them, acting as a support for the patients facing the surgical process.